Factors of Social Capital in Rural Settlements: Case of Hilvan - Tuba Inal Cekic (European Regional Science Association (ERSA), 2010)
The concept of social capital, comprising social networks, norms of reciprocity and trust, has been gaining wide interest among researchers and policy makers. So it became a common concept to use social capital as a way to both describe and understand economical, political and social wellbeing of community. While the importance of social capital is highlighted in regional and rural development strategies, Turkey has gone into a fundamental restructuring process in rural and regional development policies in terms of European Union (EU) membership process. Social capital factors in rural settlements within the context of rural development in Rural area of Hilvan, has been put forth as the main theme of this paper. The paper aims to provide an overview of the concept of social capital for rural development and discusses social capital in terms of participation, trust, openness to diversity, and social-institutional networks. Potential items to measure these elements were developed in an empirical study conducted in rural area of Hilvan. Statistical analysis has been used to define factors of social capital and relation between factors and other independent variables like characteristics of rural settlements, socio-cultural structure of rural households and agricultural property and production types.
Keywords: 330